PREPARING FOR THE INEVITABLE: LOGISTICAL CHALLENGES AND DAMAGE PROJECTIONS FOR MAJOR EARTHQUAKE IN ISTANBUL - Baskın, Tayfun; Şeker, Ayberk (Uşak Üniversitesi, 2025)
Positioned atop active fault lines, Turkey faces an imminent earthquake risk, particularly in densely populated and economically vital cities like Istanbul. This study models the potential impact of a 7.5-magnitude Marmara Earthquake on Istanbul using a coefficient-based mathematical framework derived from empirical data from the 1999 Gölcük and 2023 Kahramanmaraş earthquakes. Results estimate 105,765 fatalities, 283,355 serious injuries, and over 101,081 heavily damaged buildings across Istanbul’s districts. The projected destruction reveals a colossal post-disaster logistics burden. To address only basic needs in the first response phase, an estimated 2,392 trucks must be mobilized: 265 for tents, 69 for first aid kits, 977 for 10-day food supplies, and 1,081 for basic clothing materials. Additionally, 21,051 pieces of construction machinery will be required for debris removal and rescue operations. Emergency medical response capabilities will face severe strain: assuming each ambulance can serve two critically injured individuals, the initial response will require at least 141,678 ambulances—a number that vastly exceeds Turkey’s current medical transport capacity. These projections highlight the urgency of planning for ambulance routing systems, temporary field hospitals, and intercity medical cooperation agreements in advance. Given Istanbul’s dense urban landscape, aging building stock, and fragile infrastructure, logistical collapse is a near certainty without proactive intervention. Centralized logistics coordination centers, pre-signed agreements with logistics and demolition providers, and predefined emergency corridors in high-risk districts such as Esenyurt, Avcılar, and Küçükçekmece are essential. By offering a data-driven, scalable disaster model, this study equips policymakers and urban planners with actionable insights to prevent large-scale humanitarian crises in the aftermath of a major seismic event.

Türkiye'nin aktif fay hatları üzerinde yer alması, özellikle İstanbul gibi yüksek nüfuslu ve ekonomik açıdan kritik şehirleri büyük bir deprem riskiyle karşı karşıya bırakmaktadır. Bu çalışmada, 7,5 büyüklüğündeki olası bir Marmara Depremi'nin İstanbul üzerindeki etkileri; bina hasarı, can kayıpları ve afet sonrası lojistik gereksinimler temelinde değerlendirilmiştir. 1999 Gölcük ve 2023 Kahramanmaraş depremlerinden elde edilen ampirik verilerle oluşturulan matematiksel model, İstanbul genelinde 105.765 ölüm, 283.355 ağır yaralı ve 101.081 ağır hasarlı bina beklendiğini ortaya koymaktadır. Yapısal kayıpların ötesinde, bu senaryo acil müdahale lojistiği açısından da alarm verici düzeydedir. İlk müdahale fazında yalnızca temel ihtiyaçların karşılanması için 2.392 kamyona ihtiyaç duyulacaktır: 265 çadır kamyonu, 69 ilk yardım kamyonu, 977 gıda kamyonu ve 1.081 giyim malzemesi kamyonu sevk edilmelidir. Ayrıca, enkaz kaldırma ve kurtarma çalışmaları için 21.051 adet inşaat ekipmanı gereklidir. Tıbbi müdahale kapasitesi ise daha da dikkat çekicidir: her bir ambulansın en fazla iki ağır yaralıya hizmet edebileceği varsayımı altında, ilk 24 saatte müdahale edilebilmesi için yaklaşık 141.678 ambulansın sahada olması gerekmektedir. Bu sayı, Türkiye’nin mevcut ambulans kapasitesinin çok üzerinde olup, acil sağlık filosu planlaması, geçici sahra hastaneleri kurulumu ve şehirlerarası sağlık destek protokolleri gibi önlemlerin acilen hayata geçirilmesini zorunlu kılmaktadır. Bulgular, İstanbul'un mevcut kentsel yoğunluğu, eski yapı stoğu ve kırılgan altyapısı göz önüne alındığında; afet sonrası lojistik operasyonların hızla felce uğrayabileceğini göstermektedir. Bu doğrultuda merkezi koordinasyon merkezleri kurulmalı, özel sektörle ön sözleşmeler imzalanmalı ve yüksek riskli ilçelerde (özellikle Esenyurt, Avcılar, Küçükçekmece) acil dağıtım koridorları tanımlanmalıdır. Bu çalışma, karar vericilere yönelik veri temelli, uygulanabilir ve önleyici bir lojistik yol haritası sunarak büyük ölçekli bir insani krizin önlenmesine katkı sağlamayı amaçlamaktadır.
Kaçınılmaz Olana Hazırlık: İstanbul'da Büyük Deprem İçin Lojistik Zorluklar ve Hasar Tahminleri
Keywords: Business Systems in Context (Other); İş Sistemleri (Diğer)